2021
DOI: 10.1242/jcs.252528
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal low-density granulocytes internalize and kill bacteria but suppress monocyte function using extracellular DNA

Abstract: Low-density granulocytes (LDGs) are found abundantly in neonatal blood. However, there is limited mechanistic understanding of LDG interactions with bacteria and innate immune cells during acute infection. We aimed to determine how human neonatal LDGs may influence control of the bacterial burden at sites of infection, both individually and in the presence of mononuclear phagocytes. LDGs from human umbilical cord blood do phagocytose E. coli O1:K1:H7 and traffic bacteria into acidic compartments. However, LDGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…In a recent report, adult LDNs were shown to phagocytose opsonized latex beads at a significantly higher rate than NDNs [49]. We also demonstrated similar findings in that the frequency of neonatal LDGs capable of phagocytosing large numbers of pathogenic E. coli O1:K1:H7 is greater than neonatal NDNs [3]. However, in another study focusing on the effects of LDNs in Mtb patients, La Manna et al found that these cells did not phagocytose Mtb compared to NDNs [2].…”
Section: Disease States and Issues 231 Ldgs During Infectionsupporting
confidence: 85%
See 4 more Smart Citations
“…In a recent report, adult LDNs were shown to phagocytose opsonized latex beads at a significantly higher rate than NDNs [49]. We also demonstrated similar findings in that the frequency of neonatal LDGs capable of phagocytosing large numbers of pathogenic E. coli O1:K1:H7 is greater than neonatal NDNs [3]. However, in another study focusing on the effects of LDNs in Mtb patients, La Manna et al found that these cells did not phagocytose Mtb compared to NDNs [2].…”
Section: Disease States and Issues 231 Ldgs During Infectionsupporting
confidence: 85%
“…In our most recent publication, we describe our neonatal LDGs (from cord blood mononuclear cells, or CBMCs) as CD66 hi , CD33 + , CD14 lo , and HLA-DR − , a phenotype established in a 2013 report on neonatal gMDSCs by Rieber et al [ 3 , 7 ]. Other studies have used similar cell surface markers to characterize LDGs, gMDSCs, and LDNs ( Table 1 ).…”
Section: Bodymentioning
confidence: 99%
See 3 more Smart Citations